On the Legal Institute of Partial Nullity through the Prism of the Freedom of Contract - Midorović, Sloboda D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The paper examines the relationship between the principle of party autonomy and the institute of partial nullity of a contract. This interrelation has been brought to the spotlight due to the fact that the application of the institute of partial nullity inevitably triggers court’s intervention in the initial content of the contract, which, to be dogmatically correct, shall, in principle, be upheld by the contracting parties. This is so, given that the parties, in the specific case, may favour the elimination of their contract from the legal life over its survival in the modified text. The analysis has indicated that the stance on this subject matter cannot be uniform, since the occasions in which this relationship may come into play are not identical. Thus, this relation has been assessed in the three different sets of cases: 1) these in which the legislator a priori foresaw nullity of a specific contractual clause opting at the same time for the survival of the rest of the contract; 2) these in which the parties anticipated in their contract the influence of the nullity of a specific clause to the rest of the contract, and eventually, 3) these in which the court established the nullity of a concrete contract provision based on a general nullity clause to be found in Art. 103 in conjunction with Art. 105 of the Law on Obligations (LoO). Given that the LoO does not provide any guidelines on how the courts should handle the last group of cases, the approach advocated to this end in the legal doctrine and jurisprudence of the countries belonging to the Germanic legal family has been analysed. There, the dilemma between the partial nullity and nullity in toto is being solved with the help of the legal concept of hypothetical will. This is followed by the explanation of the concept of hypothetical will along with the legal standards and criteria according to which it shall be established. The paper concludes with the finding that the objective approach in the examining of the hypothetical will, which is advocated in the examined legal systems, is acceptable from the viewpoint of Serbian law.
Keywords: court intervention, content of the contract, hypothetical will, partial nullity, nullity in toto